Graphene Oxide Nanocomposite for Sustainable Pure Water by PES Membrane - Faneer, Khalefa A.; Mahmoudi, Ebrahim; Ba‑Abbad, Muneer; Rohani, Rosiah (Journal of Sustainability and Environmental Management, 2022)
The urgent concern of water shortage have promoted to the development of different sustainable technologies with the rapid evolution of nanotechnologies. Graphene oxide (GO) is a water-soluble material that can be constructed into a number of structures such as membranes, and has many applications in environmental sectors. Furthermore enhancing membrane characteristics to improve water flux performance and mitigate fouling is crucial issue for membrane separation technology. GO serves as nanofiller to overcome fouling during filtration as well as water flux improvement. This work aimed to develop PES membranes by phase inversion method and the fabricated membranes subjected to series analysis of FESEM, hydrophilicity and water flux. The results showed that the GO improved the contact angle of the pure PES membrane and the water flux increased from 13 to 16 L/m2.h. Therefore, the PES-GO membrane proved its capability to be used for various applications to reduce membrane fouling.